Regnum Dei Deus Est - Chilton, Bruce (Scottish journal of theology, 1978)
‘The kingdom of God’ is central in the proclamation of Jesus, the reality to which his preaching points and which the parables are designed to explicate; the student of the New Testament must understand this concept if he is to appreciate dominical theology and the ecclesial theology which developed from it. Since Albert Schweitzer's well-known study, it has been taken as a matter of course that Jesus' kingdom concept was ‘apocalyptic’. Yet just this assumption has necessitated crucial qualifications. To take two notable examples of this, Rudolf Bultmann asserted that Jesus rejected ‘the whole content of apocalyptic speculation’, and Norman Perrin went a step or two further by saying that ‘the difference between Jesus and ancient Jewish apocalyptic is much greater than Bultmann will allow’. At this point, the term ‘apocalyptic’, as applied to Jesus' preaching, is practically evacuated of content. On purely logical grounds, the propriety of its continued usage in this connexion is seriously to be questioned.